Penning the 3 AM Thoughts: What Students Say about Writing Personally in English Class. Issue 4 (3rd September 2018) - Griffith, Jason J.
ABSTRACT: This article features student perspectives on the role of personal writing in English class. Key findings and quotations are shared from two in-depth interviews with students who wrote exceptional personal essays as part of a narrative nonfiction unit in a 10th grade English class. Participants reported that writing personally generated more investment than a traditional academic assignment, controlling the level of sharing was key to being able to write honestly and openly, and mentor texts and writers' notebooks were key tools which empowered their successful writing.